Efficiency of actions in attack of diagonal players in female volleyball - Yevgeniya Strelnykova; Tamara Liakhova (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to define efficiency of technical and tactical actions of the diagonal player in the attacking actions of a team depending on schemes of a defensive play of the rival. Material & Methods: the competitive process with participation of 10 players of the role -the diagonal forward of qualification and the adult category was investigated in the pedagogical supervision. The efficiency of actions in attack of diagonal players of women's teams of Student's volleyball league of Kharkov was defined by mathematical processing of the obtained data. Results: we carried out the analysis of references on a condition of a problem of training of the diagonal player, defined tactical combinations in attack in which the diagonal player and efficiency of game actions of the diagonal player take part in the attacking actions of women's teams of Student's volleyball league of Kharkov defining indicators of efficiency of technical and tactical actions of the diagonal player in the attacking actions of women's teams of Student's league of Kharkov against various schemes of a defensive play of teams of the rival. Conclusions: the offered methodical approach based on a quantitative assessment of the competitive activity will allow to rationalize the structure and distribution of means of trainings and to increase the efficiency of the whole educational and training process of training of diagonal players for a game in attack against teams which build a defensive play according to various schemes.